2012
DOI: 10.4161/derm.22876
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the link between nutrition and skin aging

Abstract: Skin has been reported to reflect the general inner-health status and aging. Nutrition and its reflection on skin has always been an interesting topic for scientists and physicians throughout the centuries worldwide. Vitamins, carotenoids, tocopherols, flavonoids and a variety of plant extracts have been reported to possess potent anti-oxidant properties and have been widely used in the skin care industry either as topically applied agents or oral supplements in an attempt to prolong youthful skin appearance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
123
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(126 citation statements)
references
References 114 publications
0
123
0
3
Order By: Relevance
“…Very many tests and scientific experiments demonstrate that the persons who are eating a diet rich in antioxidants and take a supplement of antioxidants, live longer and healthier (Schagen et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Very many tests and scientific experiments demonstrate that the persons who are eating a diet rich in antioxidants and take a supplement of antioxidants, live longer and healthier (Schagen et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Although additional research to explain the causes and mechanisms of lycopene deficiency in ageing is required, it is clear now that correction of carotenoid deficiency in older individuals may have anenormous impact on their health status. Moreover, lycopene has to suppress activation of them TOR/AMPK cascade,a major metabolic pathway linked to ageing (Menendez et al 2013).There are numerous pieces of clinical evidence suggesting that lycopene supplementation prevents osteoporosis and incidence of bone fractures (Sacco et al 2013), improves pulmonary function (Samba et al 2012), delays skin ageing (Schagen et al 2012), and enhances physical performance in elderly patients (Alipanah et al 2009). The set of clinical consequences of lycopene deficiency is greatly enlightened by the solid body of clinical evidence revealing the crucial role of lycopene in maintaining prostate health and its ability to prevent prostate cancer in elderly males (Mariani et al 2014).…”
Section: Lycopene and Cancermentioning
confidence: 99%
“…Schagen et al [15] showed that the findings of Scarmo et al suggest that human skin, is relatively enriched in lycopene and β-carotene, compared with lutein and zeaxanthin, possibly reflecting a specific function of hydrocarbon carotenoids in human skin photoprotection.…”
Section: Beta-carotenementioning
confidence: 99%
“…Ten (10) sample preparations were done for the radical scavenging activity with ten (10) different concentrations such as 5,10,15,20,25,30,35,40,45 and 50 μg/ml.…”
Section: Plant Materials Standardized Testingmentioning
confidence: 99%